On the ontological principles in the poetological difference by Horst-Jürgen Gerigk - Argüelles Fernández, Gerardo (Acta Universitaria, 2017)
Horst-Jürgen Gerigk centers on the task of interpreting the peculiarity of the literary work with no psycho-biographical prejudices concerning the author as an individual and free of a tropological attitude, based on Heideggers’s existential concept of care (Sorge). Herein, Gerigk’s concept of poetological difference as a methodological paradigm for the interpretation of literary work is understood through an internal-external fictional description of a world already comprehended that recovers its vitality at the moment of reading.